2015
DOI: 10.1515/pjvs-2015-0093
|View full text |Cite
|
Sign up to set email alerts
|

A multiplex PCR for simultaneous detection of classical swine fever virus, African swine fever virus, highly pathogenic porcine reproductive and respiratory syndrome virus, porcine reproductive and respiratory syndrome virus and pseudorabies in swines

Abstract: In this assay, we developed and evaluated a multiplex PCR (mPCR) for its ability in detecting multiple infections of swine simultaneously. Four pairs of primers were used to detect five viruses. Specific primers were designed for classical swine fever virus (CSFV), African swine fever virus (ASFV) and pseudorabies (PRV). A pair of primers was designed prudently for two different types of porcine reproductive and respiratory syndrome virus that respectively were porcine reproductive and respiratory syndrome vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 17 publications
2
37
0
Order By: Relevance
“…By simultaneously amplifying more than one target in the same reaction, multiplex PCR increasingly is used as a rapid and convenient assay in the clinical Y. Zhao, et al Journal of Virological Methods 269 (2019) 38-42 diagnosis (Henegariu et al, 1997;Hu et al, 2015;Liu et al, 2011;Wu et al, 2013). In this study, we developed a multiplex RT-PCR assay for simultaneously detecting four viral pathogens in clinical specimens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By simultaneously amplifying more than one target in the same reaction, multiplex PCR increasingly is used as a rapid and convenient assay in the clinical Y. Zhao, et al Journal of Virological Methods 269 (2019) 38-42 diagnosis (Henegariu et al, 1997;Hu et al, 2015;Liu et al, 2011;Wu et al, 2013). In this study, we developed a multiplex RT-PCR assay for simultaneously detecting four viral pathogens in clinical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that the mRT-PCR developed is a rapid and validated method for simultaneous detection of clinical specimens. Previous reports showed that co-infection of PRRSV/CSFV and procine teschovirus (PTV) (Liu et al, 2011) or PRRSV/CSFV and pseudorabies virus (PRV) (Hu et al, 2015) was detected by mRT-PCR in clinical specimens from commercial herds in China. In our experiments, five clinical specimens exhibited co-infection of PRRSV and CSFV and one specimen co-infected with PEDV and PRRSV based on mRT-PCR detection.…”
Section: Mrt-pcr Detection Of Clinical Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…; Hu et al . ) an enzyme‐linked immunosorbent assay (ELISA) (Depner et al . ) and the immunoperoxidase test (IPT) (Pan et al .…”
Section: Introductionmentioning
confidence: 99%